INTERAKSI DISOSIATIF DALAM KONTEKS KESEHATAN SOSIAL ANAK ASUH UPTD KAMPUNG ANAK NEGERI, KOTA SURABAYA - Ade Rizkia Rahayu (JURNAL PENELITIAN KESEHATAN, 2016)
Street children and abandoned children are examples of children with social welfare issues in Surabaya. The Government of Surabaya City through the Department of Social Welfare, establish a social welfare institution for child by the name of UPTD Kampung Anak Negeri. These institutions provide alternative care to children with social welfare issues. In these institutions abandoned children, abandoned children and street children are placed together. When children are placed together, a risk of bullying among them. Therefore, researchers are searching for a deeper pattern of dissociative interaction that occurs between foster children UPTD Kampung Anak Negeri Surabaya city. The interaction patterns are further identified deeper from the standpoint of social health. Research using qualitative methods, with data collection techniques consisting of mandalam interviews, observation, and documentation. Variables examined included the characteristics of the study subjects, the action of competition, of contravention and contradiction. The results of the research found that by the age of the research subjects show patterns of social interaction dissociative, there are differences in social interaction based on time of caring and parenting backgrounds, except background research subjects as a brat. Dissociative foster child interaction patterns shown through the actions of competition, of contravention, and conflict with other foster children. Such actions show dissociative patterns of interaction that exists between foster children. The pattern of these interactions lead to a split or a pattern of bad interactions. Social health conditions should be created with good social interaction, are not optimal for their social interaction dissociative among foster children. Keyword: social interaction, social health, foster children, street children, abandoned children